Femto-Laser Assisted Cataract Surgery: A Major Review - Mahipal S Sachdev; Vineet Sehgal; Ritika Sachdev; Charu Khurana; Hemlata Gupta (Delhi Journal of Ophthalmology)
Femtosecond laser–assisted cataract surgery provides the newest innovation in field of ophthalmology that has revolutionized the way cataract surgery is performed with potential of better outcomes and safety. This article describes the femtosecond laser, surgical technique involved in femtosecond laser assisted cataract surgery and its potential benefits. The available laser platforms for commercial use are also discussed. The newer modifications and advancements in the available technology and surgical technique are reviewed that have made this technology reaching the frontiers which were earlier considered as contraindications. The results of first 100 cases done with femtosecond laser assisted cataract surgery in a tertiary eye care and referral hospital are reviewed. We have also discussed the surgical, financial, logistic challenges and opportunities that are faced by an ophthalmologist in bringing this technology as a new frontier in the world of ophthalmology.